(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
In this article, the author talked about the structure, development and psychological characteristics of students’ ability to observe in visual art classes, explained the attitude of the observer to the object of observation, as well as the conditions for organizing observation. In addition, observation is defined as the basis of visual activity.